2006
DOI: 10.1039/b610746j
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic-fluorescent nanocomposites for biomedical multitasking

Abstract: Fluorescent magnetite nanocomposites based on magnetic nanoparticles, a polyhedral octaaminopropylsilsesquioxane and a porphyrin derivative have been prepared. The intracellular uptake of the nanocomposites by macrophage and bone osteoblast cells, and their potential as MRI contrast agents, has been demonstrated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 70 publications
(45 citation statements)
references
References 20 publications
0
45
0
Order By: Relevance
“…It is also found in microwave plasma synthesized ceramic nanoparticles coated with a polymer shell [51,197,198], or coated with an organic dye [97,198,199,202]. It is one interesting property of nanoparticles with applications found primarily in medical, biological, or pharmaceutical areas [235][236][237][238][239].…”
Section: Luminescence Properties and Bifunctional Nanoparticlesmentioning
confidence: 99%
“…It is also found in microwave plasma synthesized ceramic nanoparticles coated with a polymer shell [51,197,198], or coated with an organic dye [97,198,199,202]. It is one interesting property of nanoparticles with applications found primarily in medical, biological, or pharmaceutical areas [235][236][237][238][239].…”
Section: Luminescence Properties and Bifunctional Nanoparticlesmentioning
confidence: 99%
“…Besides the biolabeling and biosensing, DDSNs can also be functionalized for drug delivery. The multifunctional DDSNs which carry photodynamic therapy agents or other anticancer drugs provide complete solutions from diagnosis and therapy [16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…17 Additionally it has been demonstrated that one dimensional linear assemblies of magnetic nanoparticles can be utilized as contrast agents in MRI studies in vivo. 18,19 In our current work we have developed new magnetic-fluorescent nanostructures, based on polyelectrolyte-stabilised magnetic nanoparticle assemblies and rhodamine B, and examined the in vitro performance of these nanostructures in primary mixed glial cell cultures.…”
Section: -16mentioning
confidence: 99%